(3JaSjQ ZQjH GdbQBf hGdMOjKs - (3Rjf GdNhGaj , eMeO Hf eMeO Hf eMeO Hf Ydj, CHh HcQ,J (B838 (3g` s
(3ChdgG (B:s
(3bGd CHh GdMSf Ydi Hf GdbGSe GdNhGai QMege Gddg gPG eG GNJUQfG ef cdGe GdYQH hCQOfG Cf jchf cJGHfG gPG Ydi YXe ZQjH GdbQBf hZQjH GdMOjK eeG PcQg CHh YHjO Ch de jPcQg s
(3BNQgG (B:s
(3jfJgi HfgGjI cJGH GdHGA , jbhd YeQ Hf GdNWGH QVi dGdg Yfg (B" (3dhdG cPG dLYdJ GdfGS HHGHkG hGMOkG Ci TF hGMOkG s
(3GdcJGH eQJH Ydi fgL GdNdjd Hf CMeO ai cJGH GdYjfs
(3hLGA ai agGQS GdecJHI hYdi UaMI ZdGa GdcJGH (B: (3cJGH eNJUQ GdYjf ai GddZIhbO UM GdTjN eMeO eMehO Hf GdJdGejO GdTfbjWi GSe GdcJGHs
(3hQO JSejJg HeNJUQ GdYjf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B214s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs